Analysis of Medication Compliance In Pulmonary Tuberculosis Patients - Media Febriana; Lilis Suryani; Dianita Ekawati; Chairil Zaman (School of Health Sciences Al-Ma'arif, 2025)
Pulmonary TB is the leading cause of death among infectious diseases. Tuberculosis patients who do not comply with taking medication with the dosage rules set by health workers will result in drug resistance or rifampicin resistance, tuberculosis patients who are said to be compliant with taking medication are able to complete treatment for 6 months or until the end of treatment. This study aims to determine drug compliance in pulmonary tuberculosis patients in Pagar Alam City in 2024. The design in this study was an analytic survey with a cross sectional design. The analysis used was univariate and bivariate analysis. The population of this study amounted to 35 people. The sampling method uses total sampling. The results showed the age variable p value 0.419, Gender p value 0.043 (OR 6,000) (CI 95% 1,274 - 28. 254), Education p value 0.031 (OR 4.667) (CI-95% 1.108 - 19.652), Employment p value 0.203, Knowledge p value 0.004 (OR 12.00) (CI95% 2.374 - 60.648), Family Support p value 0.062, Monitoring of Taking Medication (PMO) p value 0.041, Side Effects p value 0.016 (OR 7.429) (CI95% 1.555 - 35.479). The conclusion of this study is that there is an association between gender, education, knowledge, drug monitoring and side effects with drug compliance of pulmonary tuberculosis patients. On the other hand, there was no association between age, occupation, and family support with drug compliance of pulmonary tuberculosis patients. It is expected that tuberculosis patients pay more attention to their drug consumption compliance during treatment.